Marketing Mix Development Strategy In Lesehan Coffee Business In The City Of Tebing Tinggi Using Market Segmentation Priority Scale Method - Jopinus Saragih; Hendri Mayanta Tarigan (International Journal of Artificial Intelligence Research, 2022)
This study aims to find out how the Marketing Mix Development Strategy in Lesehan Coffee Business in Tebing Tinggi City Using the Market Segmentation Priority Scale Method. The results showed that the Organizational Factor variable i (X1). i has an effect on the Loyalty variable (Z). hypothesis 2 can be iseen that the variable Compensation (X2). From this description it can be seen that tcount (4.919) i> ttable (2.042), and a significance ivalue iof 0.000 i<0.05, it can be concluded that the second hypothesis is accepted, meaning that the Compensation variable (X2) affects the Loyalty variable (Z). Hypothesis 3 can be seen that ithe Organizational Factor variable (X1). X1) has no ieffect on the Performance variable (Y). hypothesis 4 can be seen that the variable Compensation (X2). From this description it can be seen that tcount (2.690) > ttable i(2.042), and a significance value of 0.012<0.05, it can be concluded that the fourth hypothesis is accepted, imeaning that the Compensation variable (X2) affects the Performance variable (Y). hypothesis 5 can be seen that the variable Loyalty i(Z). From this description it can be seen that tcount (1.891) < ttable (2.042), and a significance value of 0.069 i<0.05, iit ican ibe concluded that the fifth ihypothesis iis rejected, meaning ithat ithe Loyalty ivariable (Z) has no effect on the Performance variable (Y). Based on the results of the intervening test, it shows that the direct iinfluence of Organizational Factors (X1) on ithe Performance variable (Y) s 0.678. While the indirect effect through the Loyalty Z variable is 0.548 x 0.550 = i0.3014, the calculation results obtained show that the indirect effect through the Loyalty Z ivariable is smaller than the direct effect on the Y Performance variable. Based on the results iof the intervening test, it shows that the direct effect of compensation (X2) to Performance (Y) of 0.730 and Compensation (X2) through the variable Loyalty (Z) to Performance (Y) of 0.276 x 0.550 = 0.1518. From the calculation results obtained, it shows that the indirect effect through the Loyalty variable (Z) is greater than the direct effect on the Performance variable(Y)